1993
DOI: 10.1056/nejm199310073291501
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Perioperative Neurologic Effects of Hypothermic Circulatory Arrest versus Low-Flow Cardiopulmonary Bypass in Infant Heart Surgery

Abstract: In heart surgery in infants, a strategy consisting predominantly of circulatory arrest is associated with greater central nervous system perturbation in the early postoperative period than a strategy consisting predominantly of low-flow cardiopulmonary bypass. Assessment of the effect of these findings on later outcomes awaits follow-up of this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
380
0
9

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 650 publications
(396 citation statements)
references
References 45 publications
5
380
0
9
Order By: Relevance
“…[16][17][18][19][20] Although many improvements have been introduced since the technique was first established, there remain recognized complications secondary to unique physiologic trespasses associated with HCA and CPB. [19][20][21][22] Further refinements of the technique require an appropriate experimental model. In the present study, we developed a HCA model using rats, which was designed to mirror clinical circulatory arrest to the greatest extent possible.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Although many improvements have been introduced since the technique was first established, there remain recognized complications secondary to unique physiologic trespasses associated with HCA and CPB. [19][20][21][22] Further refinements of the technique require an appropriate experimental model. In the present study, we developed a HCA model using rats, which was designed to mirror clinical circulatory arrest to the greatest extent possible.…”
Section: Discussionmentioning
confidence: 99%
“…She also noted a lack of uniformity in type of oxygenator used (bubble vs membrane), presence of arterial line filters, electroencephalographic monitoring and kind and source of postoperative care. More recently, Newburger et al 7 reported seizures occurring in 11% of infants who had undergone a period of total circulatory arrest.…”
Section: Neurological Outcome Of Cardiopulmonary Bypassmentioning
confidence: 99%
“…The prevailing view is that chronic cyanosis and multiple cardiopulmonary bypass surgeries early in life lead to cognitive, motor, and behavioral deficits later in life (6,16). However, recent studies have implicated additional factors in the relationship between CNS abnormalities identified in neonates after birth but before surgery (17,18).…”
mentioning
confidence: 99%